Description of Paraceto gen. n. and a relimitation of the genus Cetonana (Araneae: Trachelidae) - Jin, Chi; Yin, Xiangchu; Zhang, Feng (Zootaxa, 2017)
Cetonana Strand, 1929 includes its type species, C. laticeps (Canestrini, 1868), which is redescribed, and a new species, C. shaanxiensis sp. n., is described from China. Three Brazilian species currently assigned to the genus are almost certainly misplaced. A new genus, Paraceto gen. n., is erected with the type species P. spiralis sp. n.; C. orientalis (Schenkel, 1936) is transferred to Paraceto as P. orientalis (Schenkel, 1936) comb. n..